Efectos del cambio climático en la producción agrícola - Navarro Mosquera, Rommel Darío (2025)
Food security is a challenge not only at the global and regional level, but also in Ecuador as one of the least developed countries. The study had as its main objective to analyze the impact of climate change on agricultural production. The document was prepared based on several journals, virtual libraries and the latest scientific articles. The information was obtained, interpreted, summarized and analyzed to produce relevant findings on the topic under discussion. The summary determined that the effects of climate on plant physiology have increased temperatures in response to problems of genetic erosion and plant extinction, affecting photosynthesis, respiration, water relations, membrane stability, hormonal regulation and responses of secondary metabolism of plants. It was concluded that climatic resources can damage crops through decreased productivity and yield, direct effects on plants and crops, erosion and land degradation, incidence of pests and diseases in crops and reduction of pollinators. In relation to crop resources and within this topic, climatic resources are diagnosed with low water availability, contamination, moisture loss and new pathogens introduced through new varieties. Alternatives in the crop environment, compensatory options to be carried out in the face of the challenges of climate change, refer to crop rotation with drought, temperature, salinity, abiotic stress and photoresistant or strong varieties such as chickpeas, soybeans, quinoa and beans.